Indicators of the energy supply system in the liver of rats under the conditions of different nutrients content in a diet - Voloshchuk, Oksana; Kopylchuk, Galina (My University, 2021)
The features of the energy supply in hepatocytes of rats under the conditions of different content of protein and sucrose in a diet were studied in the research. Methods. Experimental diets, differential centrifugation, spectrophotometry, chromatography on sheets. Results. It was found that 4-week maintenance of animals on a low-protein diet resulted in a 2.2-fold decrease in the succinate dehydrogenase activity, a threefold reduction of the cytochrome oxidase activity, and an increase in the F0F1-ATPase activity in a 1.5-fold in hepatocytes of rats. Under the experimental conditions, a 40 % decrease in the ATP content was found in the rat hepatocytes mitochondria against the background of an increase in the ADP content and maintaining the AMP content at the control level. It should be noted that under the conditions of the high-sucrose diet no significant changes in the succinate dehydrogenase activity were found in hepatocytes mitochondria; however, the cytochrome oxidase activity decreased by half and the F0F1-ATPase activity increased by 1.8 times. The most significant changes in the energy supply of hepatocytes occurred in the conditions of low-protein/high-sucrose diet. A sixfold decrease in the succinate dehydrogenase activity and reduction of the cytochrome oxidase activity to critically low values was found. With that, a twofold increase in the F0F1-ATPase activity compared to control was accompanied by a depletion of the pool of adenyl nucleotides. Conclusions. It is concluded that the lack of protein in the diet is a determining factor for the system of energy supply and the functioning of the respiratory chain, while the imbalance in the diet in terms of the content of food protein and sucrose is critical for the formation of an imbalance in energy supply to hepatocytes. The obtained results open up the prospects for developing a strategy of correcting energy metabolism disorders in conditions of nutritional imbalance.
Keywords: succinate dehydrogenase; сytochrome oxidase; F0F1-ATPase; liver; nutrients